Environmental Ethics Relevance in Theology Perspective: An overview from Islamic, Christian, Hindu, Buddhist, and Confucian - Sari, Indri; Karantina, Wa Ode Yessi; Lasni; Pratiwi, Ayu; Arifin, Siti Rahma (PT. Pubsains Nur Cendekia, 2024)
Environmental ethics is an important issue in the context of sustainability and environmental protection. This research aims to discuss Islamic, Christian, Hindu, Buddhist, and Confucian religious perspectives regarding environmental ethics and its importance in the context of sustainability. This research method uses literature study and analysis of sacred texts and religious teachings according to religious perspective. This research found that each religion has different views, but emphasizes the same important aspect of protecting and caring for the environment as the moral responsibility of religious communities. The concept of stewardship is emphasized considering the role of humans as managers and protectors of the universe. Environmental ethics in this religious perspective has similarities in teaching the importance of protecting and caring for the natural environment. This view can be the basis for individuals and communities to develop awareness and responsibility for environmental sustainability. Understanding and practicing religious-based environmental ethics is very relevant to overcoming the environmental challenges facing humanity in this century.